2001
DOI: 10.1046/j.1537-2995.2001.41080988.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro immunosuppressive activity of soluble HLA class I and Fas ligand molecules:do they play a role in autologous blood transfusion?

Abstract: The results of the present study are comparable with those already reported in allogeneic blood components, and they indicate that undiluted supernatants of autologous blood components may exert immunosuppressive effects in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 59 publications
5
48
1
1
Order By: Relevance
“…RBC supernatants have been shown to inhibit lymphocyte proliferative responses to mitogens and in allogeneic mixed cultures, to impair natural killer cell and cytotoxic T-cell activities, and to trigger apoptosis. 15,21,22 Nevertheless, as compared with the present findings, these inhibitory activities were detected with the use of either undiluted or relatively low dilutions of RBC supernatant. Owing to the extraordinary potency of the inhibitory activity on neutrophil chemotactic responsiveness found in RBC supernatant, attempts were made to detect whether these supernatants would also affect neutrophil locomotion.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…RBC supernatants have been shown to inhibit lymphocyte proliferative responses to mitogens and in allogeneic mixed cultures, to impair natural killer cell and cytotoxic T-cell activities, and to trigger apoptosis. 15,21,22 Nevertheless, as compared with the present findings, these inhibitory activities were detected with the use of either undiluted or relatively low dilutions of RBC supernatant. Owing to the extraordinary potency of the inhibitory activity on neutrophil chemotactic responsiveness found in RBC supernatant, attempts were made to detect whether these supernatants would also affect neutrophil locomotion.…”
Section: Discussionsupporting
confidence: 56%
“…[16][17][18][19][20] In this context, we have recently shown that nonleukodepleted stored red blood cells (RBCs) and hemoderivatives contain high levels of immunoregulatory molecules, such as soluble human leukocyte antigen (HLA) class I and Fas ligand. 21,22 These molecules have been found to inhibit mixed lymphocyte responses and cytotoxic T-cell activity in allogeneic and in autologous combinations as well as to induce apoptosis in Fas ϩ cells. 21,22 Nevertheless, the knowledge about the possibility that blood derivatives may influence the function of other cells, such as neutrophils, involved as first-line antimicrobial defenses, is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the statistically significant association with clinical parameters, the level of sHLA-I antigens has been suggested to represent a useful marker to predict the evolution of viral infections and to monitor the clinical course of allografts [7]. Moreover, elevated levels of functional sHLA-I and soluble Fas-ligand molecules have been detected by our group in blood components and might play a role in the immunomodulatory effect of autologous and allogeneic transfusions [8,9,10,11]. Several lines of evidence suggest that sHLA-I molecules are immunologically functional and may play an immunoregulatory role.…”
mentioning
confidence: 89%
“…[24] Patients receiving allogeneic blood transfusions have a higher recurrence rate of malignant tumors, decreased rates of allograft rejection and increased postoperative bacterial infections. [25,26] Thus, the immunosuppressive molecules observed in blood products may be beneficial, as in IVIg when used for treatment of autoimmune or systemic inflammatory disorders; while their potential suppressive effects in immune compromised patients has to be considered and should be further evaluated.…”
mentioning
confidence: 99%